Greek and Etruscan influences - Klicko, Ethan David (My University, 2013)
This paper is written to explore the change the Etruscans experienced by the Greeks, in regards to pottery and art forms. It will be centered on the change between early Etruscan pottery and the Villanovan period, to later periods, and how much the changes imitated the Greeks. Which is clear that they were and did emulate the Greeks in their art and pottery forms.
Keywords: Excavations (Archaeology); Greece -- History; Greece -- Antiquities; Pottery, Etruscan; Art, Etruscan; Art, Greek; Archaeology -- Methodology